Mesh and model adaptivity for flow problems - Becker, Roland; Braack, Malte; Rannacher, Rolf; Richter, Thomas (Reactive flows, diffusion and transport, 2007)
This work addresses two aspects. The first one is the practical realization of the dual weighted residual (DWR) method of Becker & Rannacher [6] to three dimensional flow problems. The second aspect is its extension to modeling errors. This gives the possibility to use on the one hand locally refined meshes, and on the other hand, a hierarchy of models in order to reduce the numerical costs without sacrifying accuracy. The issue of modeling errors is of importance in many fields, especially in reactive flow computations where sophisticated models are developed but not feasable to be used in multidimensional computations due to the high numerical costs.